Design and Evaluation of a Computerized Test for Hand Motor Skills. Issue 3 (June 2014) - Hsiao, Hsien-Sheng; Chang, Cheng-Sian; Lin, Chien-Yu; Chiu, Ching-Tsun
The purposes of this study are to design and develop a computerized test to measure junior high school students' motor skills, specifically their abilities in hand-eye motor coordination and hand motor skills, using the Wii Remote. The hand motor skills computerized test, which is based on the operational examinations in the General Aptitude Test Battery, examines hand and finger dexterity (i.e., motion, rotation, fabrication, and disassembly tests). 55 students participated in the experiment to assess the reliability and validity of the computerized test, which were supported. Information literacy and experience in the use of Wii devices did not affect the reliability.